2018
DOI: 10.15406/jdhodt.2018.09.00407
|View full text |Cite
|
Sign up to set email alerts
|

Role of CGF (Concentrated Growth Factor) in periodontal regeneration

Abstract: CGF-"A miracle in regenerative dentistry". CGF-Concentrated Growth Factor is a new regeneration platelet aggregate which is used widely in periodontal and oral surgeries. It is adopted without the use of chemicals which grades it more eco-friendly. It contains various growth factors which enhances its action and promotes wound healing. CGF is currently used along with autologous bone particles to induce bone regeneration and connective tissue attachment that shows excellent results .In future research can prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Nityasri et al [ 73 ] reported that CGF is a fibrin tissue adhesive with haemostatic and sealing properties. This provides the wound stability required to attach a new connective tissue to the root surface.…”
Section: Discussionmentioning
confidence: 99%
“…Nityasri et al [ 73 ] reported that CGF is a fibrin tissue adhesive with haemostatic and sealing properties. This provides the wound stability required to attach a new connective tissue to the root surface.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of concentrated growth factor: CGF was prepared by collecting 10 mL venous blood which was centrifuged for 4 min at 2700 rpm. After centrifugation, the layer with growth factor was carried with the instrument and adapted to the membrane [29]. The gels were loaded in 2 mL short needle syringes for ease of placement in the defect site during periodontal surgery.…”
Section: Comparative Evaluation Of the Effectiveness Of Fucoidan Cont...mentioning
confidence: 99%
“…11 Concentrated growth factor (CGF) was first explained by Sacco, L. in a lecture in 2006 as the third-generation platelet concentrate 12 and is indicated as a biological inducing material that improves the quality of the regenerated bone. 13 The fibrin network entraps platelets and leukocytes that release growth factors, enhancing bone, and soft tissue regeneration. No biochemical additives are needed to make sticky bone.…”
Section: Introductionmentioning
confidence: 99%